Phyt-dewatering of sewage sludge - Ahmed, Amira Galal (AUC Knowledge Fountain, 2019)
Over-population has resulted in an alarming rise in waste water ‎production. This lead to an increased amount of sludge and this can cause ‎serious environmental problems and health risks. This is because it carries different ‎types of pollutants. In Egypt, some sludge dewatering techniques are depending on natural evaporation (ex-ample, drying bed). However, this need very wide land areas. The other techniques are depending on mechanical ways (example, belt press)‎‏.‏‎ However, this is considered a high cost technology. ‎This research study investigated the potential efficacy of using water plants in expediting the process of sludge dewatering in drying bed. The study also proposed using aquatic plants for drying bed to improve the efficiency of both existing and newly constructed wastewater treatment plants (WWTPs) while also considering the sludge quality and cost-effective technologies and methods. The selection criteria of the plants used in the study, mainly water hyacinth (Eichhornia crassipes), common reed (phragmites), niseila (Papspalidium geminatum), and samar (Cryperus alopecuroid-es), was based on high water absorption capacity and resistance to a contaminated aquatic environment. The experiments were conducted through four phases: Phase One tested the ability of the four plants to survive in a sludge environment while Phase Two investigated which of the four plants could absorb the most water from the sludge (Phyto-dewatering); the third phase tested the surface area density of the water hyacinth, the successful plant in achieving optimum sludge evaporation. In Phase Four the design model with specific criteria (based on the first three experiments) was compared with a conventional one to test water evaporation and sludge quality. A chemical analysis of the produced sludge was conducted after each of the four phases. The results indicated that all of the selected plants were able to survive in the target environment. It was also found that water hyacinth demonstrates superior ability to consume and evaporate sludge water. Water hyacinth density is shown to be 100% effective for surface area coverage. Furthermore, results demonstrated that the design model outperformed the conventional model by 70% the quantity of evaporated sludge in half the time. It was found also that the dewatered sludge using phyto-technology more save to deal with compared ‎to sludge ‎dewatered using ordinary drying beds because the ability of water hyacinth ‎to remove the harmful microbial agents ‎from sludge such as total and fecal coliform, Salmonella, ‎Shigella and parasites.